Aplikasi Musik Orkestra Angklung Multi Oktaf Berbasis Android Dengan Sensor Accelerometer - Mardiyono Mardiyono; Noor Muhammad Rizki; Slamet Handoko (Jurnal Transformatika, 2017)
The development of android application of music instrument called Angklung is explored in several features and techniques. Previous applications allow the user to play angklung by touching and shaking, learn, answer the quiz, customize the application environment such as changing the background sound, character asset, etc. There are the problems of android angklung application including the amount of tones generally 1 octave, utilizing of accelerometer sensor, and recording system. This paper describes the development of angklung android multi octaves using accelerometer sensor. The method used is waterfall involving requirements definition, system and software design, implementation and unit testing, integration and system testing and operational and maintenance. The application is tested each functionalities (black box) and questionnaire. The result show that the application has successfully worked in android device (Jelly Bean, Kit Kat and Lollipop) that provides the innovations features to play angklung in 18 tones, play different octave by shaking the device in different way, and record the angklung orchestra sound using android. Based on the questionnaire result, the user satisfaction rate is 82.8%.